Research on the Signal Transmission System of Medical Endoscopic Ultrasound - Shao, Yuhang (International Journal of Mechanical and Electrical Engineering, 2025)
Aiming at the problem that most of the traditional medical endoscopic ultrasound signal transmission systems adopt single-pulse excitation signals, resulting in a relatively small ultrasonic transmission power and affecting the imaging quality of the system, a medical endoscopic ultrasound signal transmission system based on coded excitation technology was studied. The advantages of the encoded excitation signal over the traditional pulse excitation signal were analyzed. Four common encoded signals and their characteristics were comprehensively evaluated, and it was determined to use the Barker code as the system encoded signal. The signal transmission system was constructed by using MD1210 and TC6320. The experimental results show that this signal transmission system can effectively output the encoded excitation signal and transmit it to the ultrasonic transducer.